Long Term Results of the Modified Bentall Procedure With Mechanical and Biological Composite Valve Grafts - Werner, Paul; Gritsch, Jasmin; Kaider, Alexandra; Coti, Iuliana; Osorio, Emilio; Mahr, Stephane; Stelzmueller, Marie-Elisabeth; Kocher, Alfred; Laufer, Günther; Andreas, Martin; Ehrlich, Marek (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Despite the evident shift toward biological prostheses, the optimal choice of valve remains controversial in composite valve graft (CVG) replacement. We investigated long-term morbidity and mortality after CVG implantation in an all-comer cohort with a subgroup analysis of patients aged 50–70 years stratified after valve type. Methods: A total of507 patients underwent the Bentall procedure with either a mechanical (MCVG, n=299) or a biological (BCVG n=208) CVG replacement between 2000-2020. A single-center analysis comprising clinical and telephone follow-up was conducted to investigate late mortality and morbidity Results: The 30-day mortality in all patients (age 56±14 years, 78.1% male, EuroSCORE II 3.12 [1.7;7.1]) was 5.9%. Patients who were operated on electively had a 30-day mortality of 1.5% (n=5) while it remained higher in urgent/emergent procedures (n=25, 15.4%). Survival at 10 and 15 years was 78.19±2.26% and 72.6±3.2% respectively. In patients aged 50-70 years (n=261; MCVG=151, BCVG=110) survival did not differ significantly between the valve groups (p=0.419). Multivariable analysis showed no significant impact of valve type on survival (p=0.069). A time-varying relation with survival was notable, showing a higher risk in the MCVG group in the early postoperative phase, which declined compared to the BCVG group in the course of follow-up. Conclusions: The Bentall technique presents with excellent mortality when performed electively. The type of valve prosthesis showed no statistically significant effect on mortality in patients aged 50-70 years, however, a time-varying relation showing an initially higher risk with MCVG which decreased compared to BCVG at long-term follow-up was notable. Further studies with even longer follow-up of BCVGs will clarify the ideal choice of prosthesis in this patient subset.